Determination of salicylate in blood serum using an amperometric biosensor based on salicylate hydroxylase immobilized in a polypyrrole-glutaraldehyde matrix - Rover Júnior, Laércio; Oliveira Neto, Graciliano de; Fernandes, João Roberto [UNESP]; Kubota, Lauro Tatsuo (Elsevier B.V., 2000)
The use of an amperometric biosensor for the salicylate determination in blood serum is described. The biosensor is based on salicylate hydroxylase (EC 1.14.13.1) electropolymerized onto a glassy carbon-working electrode with polypyrrole and glutaraldehyde, to improve the biosensor lifetime. The hexacyanoferrate (II) was also incorporated to work as a redox mediator to minimize possible interferences. The salicylate is enzymatically converted to catechol, which is monitored amperometrically by its electrooxidation at +0.170 V versus SCE (saturated calomel electrode). Salicylate determination was carried out maintaining the ratio between β-NADH and salicylate at 4:1 (30°C). The amperometric response of the biosensor was linearly proportional to the salicylate concentration between 2.3 x 10-6 and 1.4 x 10-5 mol l- 1, in 0.1 mol l-1 phosphate buffer (pH 7.8), containing 0.1 mol l-1 KCl and 5.0 x 10-4 mol l-1 Na2H2EDTA, as supporting electrolyte. The recovery studies, in the presence of several interfering compounds, showed recoveries between 96.4 and 104.8%. The useful lifetime of the biosensor in the concentration range evaluated was at least 40 days, in continuous use. Blood serum samples analyzed by this biosensor showed a good correlation compared to the spectrophotometric method (Trinder) used as reference, presenting relative deviations lower than 7.0%. (C) 2000 Elsevier Science B.V.
Keywords: Polypyrrole; Salicylate determination; Salicylate hydroxylase; Serum samples; Buffer; Carbon; Catechol; Electrolyte; Ferrocyanide; Glutaraldehyde; Mercurous chloride; Oxygenase; Phosphate; Polypyrrole; Reduced nicotinamide adenine dinucleotide; Salicylic acid; Amperometry; Biosensor; Blood analysis; Chemical composition; Controlled study; Drug determination; Electrode; Intermethod comparison; Oxidation; pH; Polymerization; Serum; Spectrophotometry; Temperature